The impacts of critical metal shortage on China's electric vehicle industry development and countermeasure policies. (1st June 2022) - Liu, Boyu; Zhang, Qi; Liu, Jiangfeng; Hao, Yawei; Tang, Yanyan; Li, Yaoming
Abstract: Electric vehicle (EV) has been taken as the key technology in the road transportation sector to achieve the carbon neutrality target. However, considering China's critical metal resource endowment as well as its supply status, the potential metal supply shortage and its impact on China's EV industry development goal need to be analyzed. Therefore, in the present study, several supply and recycling scenarios are proposed and a dynamic stock-flow model is adopted to calculate the impacts of potential critical metal shortages including nickel, cobalt, and lithium and their countermeasures. The obtained results show that: i) The current resource endowment in China cannot meet the metal demand for EV industry development target. From 2022 to 2050, the metal shortage will cut the accumulative EV production potential by 459.7–384.6 million units, leading to extra greenhouse gas emissions; ii) In terms of specific metal types, the shortage of lithium will occur in 2026 and 2034 under different metal supply scenarios, which will hinder the EV production significantly; iii) In total, there are 101.9–190.8 Kt, 20.3–38.1 Kt, and 40.2–78.9 Kt nickel, cobalt, and lithium resource can be obtained from battery recycling system under different scenarios. However, the metal shortage issue still exists even under the highest recycling ratio scenario. The findings of this study are significant for policymakers to further understand the nexus between emission abatement and mineral conservation in the process of EV industry development and propose relevant policies. Highlights: The critical metal resource demand-supply in China's EV industry is evaluated using a dynamic stock-flow model. Current mineral resource endowment cannot sustain the resource demand for EV industry development in China. Lithium shortage will occur in 2026 and 2034 under the low and high metal supply scenarios respectively. Battery recycling strategies will work in the long run, but cannot fully solve the metal shortage issue.